Sustainable Food Reserve Program as Policy Intervention for Food and Nutrition Security in East Java, Indonesia: Roles of Officials and Local Actors - Apri Kuntariningsih; Siswanto Imam Santoso; Joko Mariyono (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2023)
This paper analyses the implementation of a sustainable food reserve program that empowers the community by mitigating the adverse impacts of malnutrition in Indonesia. This paper adopted an actor- and institution-centered communication approach to analyze the stakeholders, directly and indirectly, engaged in implementing the program. East Java province was selected as the sample of the study. Results of the analysis show that the communications of actors and institutions played dominant roles in the program implementation. In the early implementation stage, the dominant roles of actor and institution communication were strongly required in a new program intervention to guarantee smooth implementation. Government officials played a significant communication role at the provincial level. At the grassroots level, the main actors were women leaders of household prosperity education and farmer leaders. Agricultural extension officials dominantly communicated between provincial and grassroots levels. Institutions must start reducing dominant roles and appointing local cadres to replace and reduce dependency on the institutions.